Medieval English in a Multilingual Context Current Methodologies and Approaches - Pons-Sanz, Sara M.; Sylvester, Louise (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This edited book examines the multilingual culture of medieval England, exploring its impact on the development of English and its textual manifestations from a multi-disciplinary perspective. The book offers overviews of the state of the art of research and case studies on this subject in (sub)disciplines of linguistics including historical linguistics, onomastics, lexicology and lexicography, sociolinguistics, code-switching and language contact, and also includes contributions from literary and socio-cultural studies, material culture, and palaeography. The authors focus on the variety of languages in use in medieval Britain, including English, Old Norse, Norn, Dutch, Welsh, French, and Latin, making the argument that understanding the impact of medieval multilingualism on the development of English requires multidisiplinarity and the bringing together of different frameworks in linguistics and cultural studies to achieve more nuanced answers. This book will be of interest to academics and students of historical linguistics and medieval textual culture. Sara M. Pons-Sanz is Reader in Language and Communication at Cardiff University, UK. She led the AHRC-funded network Medieval English (ca600-1500) in a Multilingual Context and co-led the AHRC-funded Gersum Project. She is the author of The Lexical Effects of Anglo-Scandinavian Linguistic Contact on Old English, and other books and articles on medieval English. Louise Sylvester is Professor of English Language at the University of Westminster, UK. She co-edited the Bilingual Thesaurus of Everyday Life in Medieval England and the multilingual database Lexis of Cloth and Clothing in Britain c700-1450. She has published widely on the effects of contact with French on the vocabulary of Middle English.
Keywords: Historical linguistics; Linguistics -- Methodology; Multilingualism; Europe -- History -- 476-1492.; Lexicology; Historical Linguistics; Research Methods in Language and Linguistics; Multilingualism; History of Medieval Europe; Lexicolopgy / Vocabulary